Effect of corrosion and sandblasting on the high cycle fatigue behavior of reinforcing B500C steel bars - Marina C. Vasco; P. Polydoropoulou; Apostolos N. Chamos; Spiros G. Pantelakis (Fracture and Structural Integrity)
In a series of applications, steel reinforced concrete structures are subjected to fatigue loads during their service life, what in most cases happens in corrosive environments. Surface treatments have been proved to represent proper processes in order to improve both fatigue and corrosion resistances. In this work, the effect of corrosion and sandblasting on the high cycle fatigue behavior reinforcing steel bars is investigated. The investigated material is the reinforcing steel bar of technical class B500C, of nominal diameter of 12 mm. Steel bars specimens were first exposed to corrosion in alternate salt spray environment for 30 and 60 days and subjected to both tensile and fatigue tests. Then, a series of specimens were subjected to common sandblasting, corroded and mechanically tested. Metallographic investigation and corrosion damage evaluation regarding mass loss and martensitic area reduction were performed. Tensile tests were conducted after each corrosion exposure period prior to the fatigue tests. Fatigue tests were performed at a stress ratio, R, of 0.1 and loading frequency of 20 Hz. All fatigue tests series as well as tensile test were also performed for as received steel bars to obtain the reference behavior. The results have shown that sandblasting hardly affects the tensile behavior of the uncorroded material. The effect of sandblasting on the tensile behavior of pre-corroded specimens seems to be also limited. On the other hand, fatigue results indicate an improved fatigue behavior for the sandblasted material after 60 days of corrosion exposure. Martensitic area reductions, mass loss and depth of the pits were significantly smaller for the case of sandblasted materials, which confirms an increased corrosion resistance